(untitled) (International Journal of Food and Nutritional Sciences, 2023)
A field experiment were conducted for two consecutive rabi seasons during 202-23 and 2023-24 at Agriculture farm, Rama University Kanpur on gangatic alluvial soil having 7.6 pH, light textured soil with medium soil fertility. Treatments comprises of viz., three preparatory tillage T1 - one cross ploughing with cultivator, T2 - one ploughing with disc harrow + one cross ploughing with cultivator and T3- one ploughing with disc harrow + one pass with rotavator, three nutrient management practices i.e. N1-100% RDF (60 Kg N ha-1 + 30 Kg P2O5 ha-1+ 30 Kg K2O ha-1 ) through chemical fertilizer, N2-75% RDF( through chemical fertilizer) + 25% FYM (Farm yard manure) and N3-50% RDF (through chemical fertilizer) +50% FYM (Farm yard manure) and three moisture conservation practices viz., 1) M1- Control, 2) Research was done on M2-Dust mulch and M3-Pinoxaden 5.1 EC @ 50 g a.i ha-1 + VAM @ 15 Kg ha-1. The findings of the two-year experiment show that planting barley in plots with preparatory tillage, T3 (one ploughing with a disc harrow and one pass with a rotavator), nutrient application as N3-50% RDF through chemical fertiliser + 50% FYM, and moisture conservation techniques of M3-pinoxaden 5EC @ 50 g/ha. + VAM @ 15 kg/ha, respectively, produced the highest values of growth parameters, yield attributes, and the days of flowering and maturity of barley during the two study years. T1 was then planted with a cultivator and N1-100% RDF (60 Kg N ha-1 + 30 Kg P2O5 ha-1 + 30 Kg K2O ha-1) through chemical fertiliser and a-1+ 30 Kg K2O ha-1 ) through chemical fertilizer